Using Nanoparticles as Antibacterial Agents by Taking Advantage of Plasmonic Thermal Effects (Eurasian Journal of Research, Development and Innovation, 2024)
The study focused to synthesize and evaluate the thermo-plasmonic properties based on the core/multi-shell nanoparticles prepared by laser ablation in liquids with nanosecond laser pulses at 1064 nm, to introduce a new type of hybrid nanostructures usable in biomedicine and optical photonics applications. For these hybrid nanostructures, Gold and Silver as a partner of Silicon were used in thermo-plasmonic part, the hybrid multishell nanostructures consist of gold-silver and silver-gold sandwich with silicon shell in between.The optical absorption was measured using aUV–Vis spectrophotometer for the samples. In addition, the thermo-plasmonic properties are studied by monitoring the local temperature increase of the samples experimentally by infrared camera, when the samples are illuminated by lasers of different wavelengths (532, 405 nm). As well as the core/multi-shell NPs were tested to inhibit the activity of the E-coli bacteria under laser radiation.In addition, the results show that not only an extreme tunability in the surface plasmon resonances can be obtained, but also considerably enhanced photo-thermal effects in terms of temperature rise, that depends on the laser effect